GlnR positively affects the acid resistance of Lactiplantibacillus plantarum from wine by regulating glutamate metabolism - Lu, Ke; Shi, Kan; Yuan, Yuxin; Liu, Yuanyuan; Miao, Chuangyi; Pan, Tao; Duan, Pengfei; Wang, Jangyong; Liu, Shuwen; Zhao, Lili (Frontiers in Microbiology, 2026)
IntroductionOwing to its remarkable capacity to modify the aroma profile of wine, Lactiplantibacillus plantarum (L. plantarum) derived from wine has emerged as a potential starter for malolactic fermentation. However, the inadequate acid resistance of this bacterium severely restricts its application. In some bacterial species, GlnR is considered a universal transcriptional regulator in response to acid stress.MethodsIn this study, we determined the function of GlnR in the acid resistance of L. plantarum for the first time. RT-qPCR and yeast one-hybrid assays revealed a direct regulatory correlation between GlnR and genes associated with the glutamate metabolic pathway. Metabolomics analysis via liquid chromatography-mass spectrometry and fermentation studies confirmed that GlnR affected γ-aminobutyric acid (GABA) production.ResultsThe growth and survival rate of the knockout strain XJ25-ΔglnR were significantly lower than those of the wild-type strain XJ25. GlnR can directly bind to the promotor regions of the genes glnA, gadB, and glms1, thereby upregulating gadB transcription while downregulating glnA and glms1 transcription, directing the increased metabolic flux toward GABA synthesis.DiscussionWe present evidence that GlnR plays a vital role in the glutamate metabolic pathway and is a positive transcriptional regulator that can control the acid resistance of L. plantarum XJ25. Although GlnR interacts with glnA, gadB, and glms1, additional studies are warranted to determine how this interaction affects its acid resistance.